2016
DOI: 10.1111/tmi.12798
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) awareness and vaccine receptivity among Senegalese adolescents

Abstract: Objective To examine HPV vaccine awareness and receptivity among adolescents and young adults in Senegal. Methods Participants from 6 high schools and 5 community centers across five regions of Senegal (n=2,286) completed a self-administered questionnaire in October and November 2014. The study assessed HPV awareness and receptivity toward receiving the HPV vaccine. Multivariable logistic regression explored statistically significant relationships between the predictor variables and both outcomes. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
(28 reference statements)
4
22
1
Order By: Relevance
“…Numerous previously reported surveys have demonstrated that 50% to 85% of women know about cervical cancer in Asia, 17 , 18 which is in accordance with the observations of our study. Human papillomavirus awareness was higher in Denmark (75.8%) and Sweden (74.8%) compared with Norway (62.4%) and Senegal (63%), 19 , 20 while studies from Yunnan, China (52.6%), Xinjiang, China (0.14%, 10 out of 7100), and Brazil (37%) have reported low levels of knowledge and awareness about HPV that are consistent with the findings of this study. 13 , 21 , 22 However, the levels of knowledge and awareness about HPV observed in the present study are higher than those in previously reported studies 13 , 23 but are still low.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous previously reported surveys have demonstrated that 50% to 85% of women know about cervical cancer in Asia, 17 , 18 which is in accordance with the observations of our study. Human papillomavirus awareness was higher in Denmark (75.8%) and Sweden (74.8%) compared with Norway (62.4%) and Senegal (63%), 19 , 20 while studies from Yunnan, China (52.6%), Xinjiang, China (0.14%, 10 out of 7100), and Brazil (37%) have reported low levels of knowledge and awareness about HPV that are consistent with the findings of this study. 13 , 21 , 22 However, the levels of knowledge and awareness about HPV observed in the present study are higher than those in previously reported studies 13 , 23 but are still low.…”
Section: Discussionsupporting
confidence: 88%
“…[20][21][22][23][24] A study by Massey et al indicated low awareness of HPV; among those who had heard of HPV, just 28% were willing to receive the HPV vaccine. 25 Overall vaccination rates were very low in our sample cohort. Only 5.5% of the participants had been vaccinated against HPV.…”
Section: Discussionmentioning
confidence: 65%
“…Nine included studies assessed the awareness of 5,157 Africans in regard to HPV, four studies were conducted in Nigeria [35,36,41] and one in each of Madagascar, Morocco, Mali, South Africa and Senegal [43,49,51,54,70,71] . The oldest among the study included was conducted in 2010 while the newest was conducted in 2016 (Table 1).…”
Section: Resultsmentioning
confidence: 99%